2016
DOI: 10.1088/0741-3335/58/3/034010
|View full text |Cite
|
Sign up to set email alerts
|

Pico-coulomb charge measured at BELLA to percent-level precision using a Turbo-ICT

Abstract: Precise diagnostics of picocoulomb level particle bunches produced by laser plasma accelerators (LPAs) can be a significant challenge. Without proper care, the small signals associated with such bunches can be dominated by a background generated by laser, target, laser-plasma interaction and particle induced radiation. In this paper, we report on first charge measurements using the newly developed Turbo-ICT for LPAs. We outline the Turbo-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The laser beam is focused in the leading edge of a 4 × 1 mm rectangular supersonic nozzle along the longer direction. The charge of electron bunch is measured by Turbo Integrating Current Transformer (Turbo‐ICT) [ 22 ] out of 100 μm beryllium (Be) window. The energy spectra of electron bunch are analyzed by a magnetic spectrometer with field intensity of 0.8 T, which permits a detection range of minimal energy of 68 MeV while keeping an acceptable resolution in 300 MeV.…”
Section: Results Ans Discussionmentioning
confidence: 99%
“…The laser beam is focused in the leading edge of a 4 × 1 mm rectangular supersonic nozzle along the longer direction. The charge of electron bunch is measured by Turbo Integrating Current Transformer (Turbo‐ICT) [ 22 ] out of 100 μm beryllium (Be) window. The energy spectra of electron bunch are analyzed by a magnetic spectrometer with field intensity of 0.8 T, which permits a detection range of minimal energy of 68 MeV while keeping an acceptable resolution in 300 MeV.…”
Section: Results Ans Discussionmentioning
confidence: 99%
“…Further research showed that residual EMP within a narrow frequency bandwidth was the primary limit on ICT sensitivity for Q < 5 pC. Frequency filtering of the ICT's signal processing electronics improved sensitivity to the sub-pC level, while improving noise immunity and retaining excellent cross-calibration with other detectors (Nakamura et al, 2016). The filtered ICT has been marketed, an example of commercial product development spurred by plasma accelerator diagnostics research.…”
Section: Total and Spatially-resolved Charge Measurementmentioning
confidence: 99%
“…The dipole magnet spectrometer (Brown, 1975) is the workhorse for single-shot measurement of electron energy spectra both in conventional (Brown, 1975) and plasmabased (Glinec et al, 2006;Nakamura et al, 2008;Sears et al, 2010b) accelerators. Plasma-based electron accelerators, however, pose two special challenges.…”
Section: Mev and Gev Magnetic Spectrometersmentioning
confidence: 99%
See 2 more Smart Citations